A dual‐band eight‐antenna multi‐input multi‐output array for 5G metal‐framed smartphones. Issue 7 (1st April 2019) - Zou, Huanqing; Li, Yixin; Xu, Bin; Luo, Yong; Wang, Mingkai; Yang, Guangli
Abstract: A dual‐band eight‐antenna array operating in the long‐term evolution (LTE) band 41 (2.496‐2.69 GHz) and 3.5‐GHz band (3.3‐3.7 GHz) for fifth‐generation (5G) metal‐framed smartphone is presented. The proposed dual‐band antenna array is composed of four identical dual‐antenna building blocks (DABBs). Each DABB consists of two identical antenna elements with a neutralization line between them. The antenna array is simulated, fabricated, and measured. The isolations are better than 10.5 dB and 11.0 dB in the low band (LB; LTE band 41) and high band (HB; 3.5‐GHz band). The total efficiencies are 41% to 54% and 46% to 64% in the two operation bands, respectively. In addition, the measured envelope correlation coefficients are less than 0.11 and 0.06, the calculated channel capacities are better than 34.5 and 36.3 bps/Hz in the LB and HB, respectively. Furthermore, four hand‐grip scenarios are investigated, and results show that proposed antenna array can maintain excellent multiple‐input multiple‐output performances in all scenarios.